(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes issues related to the types of witness immunity in criminal proceedings and its specific characteristics. Most importantly, the right to immunity is divided into three types according to the scope of use: complete; limited and mixed. In this article, along with national and foreign legislation, the opinions of scientists are also analyzed.